The transformations of sciences under the digital regime - Vinck, Dominique (Instituto de Altos Estudios Sociales, 2018)
Knowledge production is intimately related to the elaboration and circulation of written texts. The passage from print to electronic format, from papers to digital files in a network, has notably transformed scientific researchers practices. But what has changed fundamentally in the digital age? This article addresses important transformations that have been consolidated in the digitalization of scientific production, it also discusses the emergence of alternative practices to access and share knowledge in this new context.